Central banking and monetary policy in Sri Lanka - Karunatilake, H. N. S. (Colombo : Lake House Investments, 1973)
This book complements the earlier book entitled Banking and financial institutions in Ceylon, by the author, and in some ways in a sequel with considerably emphasis on the diversified activities of the Central Bank
Running title: Central banking in Sri Lanka.
"
Includes bibliography: p. 207-209.
hza 28/01/2019
Loans
Keywords: Banks and banking, Central; Monetary policy